Endoscopic diagnosis of Helicobacter pylori gastritis using white light imaging and texture and color enhancement imaging - Kitagawa, Yoshiyasu; Koga, Kunishige; Ishigaki, Asuka; Nishii, Rino; Sugita, Osamu; Suzuki, Takuto (Endoscopy International Open, 2023)
Background and study aims Texture and color enhancement imaging (TXI) is a new image-enhanced endoscopy that augments subtle tissue differences and color changes in gastric mucosa. This study aimed to compare the usefulness of TXI and white light imaging (WLI) for diagnosing Helicobacter pylori gastritis.Patients and methods We retrospectively prepared one image set with 22 endoscopic images acquired by WLI and TXI from 60 consecutive patients individually. Five endoscopists independently reviewed the randomly displayed image sets and assessed the H. pylori infection status on endoscopy according to the Kyoto Classification of Gastritis. The primary endpoints were the accuracies of WLI and TXI in diagnosing H. pylori-active gastritis. The correlation of the endoscopic features with the three H. pylori infection statuses (current infection, past infection, and noninfection) was also evaluated.Results Diagnostic accuracy for active gastritis was significantly higher in TXI than in WLI (85.3 % vs. 78.7 %; P = 0.034). All the specific endoscopic features associated with H. pylori infection statuses had a higher odds ratio with TXI than with WLI. Additionally, interobserver agreement among the five reviewers was higher in TXI than in WLI, except for one pair.Conclusions TXI may improve the endoscopic diagnosis accuracy for H. pylori infection.